Evaluating the mating competency of genetically modified male mosquitoes in laboratory conditions - Contreras, Bryan; Adelman, Zach N.; Chae, Keun (Frontiers in Tropical Diseases, 2023)
Efforts to eradicate mosquito-borne diseases have increased the demand for genetic control strategies, many of which involve the release of genetically modified (GM) mosquito males into natural populations. The first hurdle for GM males is to compete with their wild-type counterparts for access to females. Here, we introduce an eye color-based mating assay, in which both Lvp wild-type and kynurenine 3-monooxygenase (kmo)-null males compete for access to kmo-null females, and therefore the eye color phenotype (black or white) of the progeny is dependent on the parental mating pair. A series of tests addressed that male mating competitiveness between the two strains can significantly be influenced by adult density, light intensity, and mating duration. Interestingly, the mating competitiveness of males was not correlated with body size, which was negatively influenced by a high larval density. Lastly, this eye color-associated assay was applied to characterize GM mosquitoes in their mating competitiveness, establishing this method as a fast and precise way of benchmarking this fitness parameter for laboratory-raised males.